Intranasal lipid nanocapsule administration of the new lipophenol quercetin-3-O-DHA-7-O-iPr reduces carbonyl stress and improves behavior in a mouse model of Alzheimer’s disease - Léa Otaegui; Jordan Lehoux; Sylvie Begu; Tristan Moujellil-Legagneur; Charleine Zussy; Mathieu Vitalis; Magalie Mathias; Annaëlle Beau; Thierry Durand; Laurent Givalois; Nathalie Bernoud-Hubac; Céline Crauste; et al. (Drug Delivery and Translational Research, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Intraslab seismicity migration simultaneously with an interface slow slip event along the Ecuadorian subduction zone - Alexander Wickham-Piotrowski; Yvonne Font; Marc Regnier; Bertrand Delouis; Jean-Mathieu Nocquet; Louis De Barros; Virginie Durand; Quentin Bletery; Monica Segovia (Tectonophysics, 2024)

Analyzing Socio-Metabolic Vulnerability: Evidence from the Comoros Archipelago - Jean-Baptiste Bahers; Simron Singh; Mathieu Durand (Anthropocene Science, 2022)

Urban Metabolism of Intermediate Cities: The Material Flow Analysis, Hinterlands and the Logistics‐Hub Function of Rennes and Le Mans (France) - Jean‐Baptiste Bahers; Sabine Barles; Mathieu Durand (Journal of Industrial Ecology, 2019)
Summary Although urban metabolism has been a subject of renewed interest for some years, the related studies remain fragmented throughout the world. Most of them concern major cities (megacities and/or national capitals) and, more rarely, intermediate, medium‐sized or small cities. However, urbanization trends show that together with the metropolization process, another one is characterized by the proliferation of intermediate cities. We have studied the metabolism of two French intermediate cities for the year 2012: Rennes Métropole (400,000 inhabitants) and Le Mans Métropole (200,000 inhabitants). To this end, we used material flow analysis (MFA) based on the methodology developed by Eurostat, adapted to the subnational level. This has been made possible by the use, for the first time, of very precise statistical sources concerning freight. We have developed a multiscale approach in order to weigh the urban metabolism of those two cities and to compare it to other cases and larger territories. This allows a better understanding of the specific territorial metabolism of intermediate cities, their hinterlands, and their logistics‐hub function. We conclude with the “urban dimension” of social metabolism, and, thanks to the multiscale approach, to the debate regarding logistical hubs, dematerialization, and territorial autonomy.

Reassessment of the size of the Scopoli’s Shearwater population at its main breeding site resulted in a tenfold increase: implications for the species conservation - Pierre Defos du Rau; Karen Bourgeois; Mathieu Thévenet; Lise Ruffino; Sylvain Dromzée; Ridha Ouni; Awatef Abiadh; Roger Estève; Jean-Patrick Durand; Lorraine Anselme; Gilles Faggio; Jaber Mohamed Yahya; et al. (Journal of Ornithology, 2015)